Penggunaan media kliping berbasis project based learning pada pembelajaran ipa untuk meningkatkan keterampilan berpikir kreatif siswa kelas V sekolah dasar - Twiningsih, Anik (Jurnal Pendidikan Dasar, 2022)
This study aims to describe the use of Project Based Learning-based clipping media in science learning to improve the creative thinking skills of fifth grade students. The method used in this study is a descriptive qualitative research method with an observation approach. The source of the research data was obtained from the teacher's observations during the learning process using clipping media and empowering the PjBL model. The learning outcomes presented in this study were the learning outcomes from the skill aspect, namely students' creative thinking skills in solving science learning problems presented by the teacher. From the research results, it was found that by using Project Based Learning clipping media, students' creative thinking skills increased. Creative thinking skills that are measured include 4 indicators, namely fluency, flexibility, originality, and elaboration. The results of students' creative thinking skills using PjBL-based clipping media are as follows: fluency (fluency) 85% completeness, flexibility (flexibility) 80% completeness, originality (originality) 87% completeness, and elaboration (detail) 88% completeness.